2002
DOI: 10.1046/j.1440-6047.2002.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienols are needed for normal bone calcification in growing female rats

Abstract: In this study the effects of vitamin E deficiency and supplementation on bone calcification were determined using 4-month-old female Sprague-Dawley rats. The rats weighed between 180 and 200 g. The study was divided in three parts. In experiment I the rats were given normal rat chow (RC, control group), a vitamin E deficient (VED) diet or a 50% vitamin E deficient (50%VED) diet. In experiment 2 the rats were given VED supplemented with 30 mg/kg palm vitamin E (PVE30), 60 mg/kg palm vitamin E (PVE60) or 30 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 17 publications
3
33
0
2
Order By: Relevance
“…Norazlina et al indicated that vitamin E was essential for normal calcium metabolism. Rats receiving vitamin E-deficient diet suffered from increased parathyroid level, impaired calcium absorption and low calcium content in the lumbar spine [35,36]. Supplementation with gamma-tocotrienol could preserve the calcium content in rats fed with vitamin E-deficient diet [37].…”
Section: Discussionmentioning
confidence: 99%
“…Norazlina et al indicated that vitamin E was essential for normal calcium metabolism. Rats receiving vitamin E-deficient diet suffered from increased parathyroid level, impaired calcium absorption and low calcium content in the lumbar spine [35,36]. Supplementation with gamma-tocotrienol could preserve the calcium content in rats fed with vitamin E-deficient diet [37].…”
Section: Discussionmentioning
confidence: 99%
“…Tocotrienol mixture at 60-and 100-mg/kg body weight restored free radical-induced reduction in serum level of osteocalcin, the number of osteoblasts, and bone formation in male Wistar rats while reducing the level of bone-resorbing cytokines [82]. Oral intake of γ-tocotrienol [91,166] and a mixture of tocotrienols [91,92] increased bone calcification in Sprague-Dawley rats. A tocotrienol-enhanced fraction and γ-tocotrienol also counteracted the nicotine effect on bone resorption in rats [83].…”
Section: Tocotrienols: In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…In all the comparison studies, α-tocopherol [91,92,166,169], tocopherols [169] and tocopheryl esters [82,91] with no mevalonate suppressive activity [63] offer either no protection or less-thantocotrienol effects [83,170,171]. γ-Tocotrienol at 60 mg/kg decreased trabecular separation and increased trabecular bone volume and thickness, trabecular number, load value, displacement, stress value, strain value, viscoelasticity and stiffness in male rats to significantly greater extent than did equal dose of α-tocopherol [88].…”
Section: The Differential Impacts Of Tocotrienols and Tocopherolsmentioning
confidence: 99%
“…Gamma tocotrienols, shown to prevent the loss of bone mineral density, reduce osteoporosis, reduce body fat mass and improve the bone calcium content of rats [108,109]. Both tocotrienol and tocopherol have the potential to be developed as an antiosteoporotic agent.However, tocotrienol has been shown to be superior than tocopherol and is a better candidate for human studies [110].…”
Section: Bone Mineral Densitymentioning
confidence: 99%